The Urgency of Comprehensive and Integrated Digital Asset Regulation - Francisca Romana Nanik Alfiani (Journal of Social Science, 2024)
Cryptocurrency has grown rapidly since it was first introduced to the public. Many countries, including Indonesia, have begun to adopt special regulations for cryptocurrencies in response to the exponential growth and penetration of cryptocurrencies in the traditional financial system. Regulations aim to protect investors, ensure economic stability, and prevent illegal activities such as terrorism, money laundering and tax evasion. In January 2023, Law Number 4 of 2023 concerning Development and Strengthening of the Financial Sector ("UU P2SK") was enacted as a form of financial sector reform. Starting January 2025, regulation and supervision of cryptocurrency transactions will be carried out by the Financial Services Authority (OJK) replacing the Commodity Futures Trading Supervisory Agency (Bappebti) which has established several regulations regarding Crypto assets. But until now There are no regulations regarding permits or prohibitions for influencers/celebrities in marketing crypto assets via social media or other media to the public even though these regulations are needed to mitigate the incidence of victims and losses, as in several cases that have occurred. In the future, a comprehensive and integrated regulation is needed with other laws and regulations such as the Terrorism Law, the Money Laundering Crime Law, the Consumer Protection Law, the ITE Law, the Criminal Code and other related laws and regulations, in order to keep up with the rapid development of cryptocurrency and the changing character of the digital world. global and borderless.